2010
DOI: 10.1029/2010ja015915
|View full text |Cite
|
Sign up to set email alerts
|

Self‐consistent inner magnetosphere simulation driven by a global MHD model

Abstract: [1] We present results from a one-way coupling between the kinetic Ring Current Atmosphere Interactions Model with Self-Consistent B field (RAM-SCB) and the Space Weather Modeling Framework (SWMF). RAM-SCB obtains plasma distribution and magnetic field at model boundaries from the Block Adaptive Tree Solar Wind Roe Upwind Scheme (BATS-R-US) magnetohydrodynamics (MHD) model and convection potentials from the Ridley Ionosphere Model within SWMF. We simulate the large geomagnetic storm of 31 August 2005 (minimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 77 publications
0
57
0
Order By: Relevance
“…Large magnetic field depressions have been measured at distances as small as 3-4 Earth radii (R E ) during major geomagnetic storms (Dst < 250 nT) and have been associated with the storm time ring current enhancement (e.g., Cahill 1966;Tsyganenko et al 2003). Sophisticated physics-based models (e.g., Chen et al 2006a;Zaharia et al , 2010 have been developed to investigate the effect of plasma pressure on the magnetic field in the inner magnetosphere during magnetic storms. The computed magnetic field and electric currents showed that plasma pressure strongly affects the B-field, even very close to Earth, and large field depressions develop near Earth at the storm peak.…”
Section: How Do Ring Current and Other Geomagnetic Processes Affect Rmentioning
confidence: 99%
See 2 more Smart Citations
“…Large magnetic field depressions have been measured at distances as small as 3-4 Earth radii (R E ) during major geomagnetic storms (Dst < 250 nT) and have been associated with the storm time ring current enhancement (e.g., Cahill 1966;Tsyganenko et al 2003). Sophisticated physics-based models (e.g., Chen et al 2006a;Zaharia et al , 2010 have been developed to investigate the effect of plasma pressure on the magnetic field in the inner magnetosphere during magnetic storms. The computed magnetic field and electric currents showed that plasma pressure strongly affects the B-field, even very close to Earth, and large field depressions develop near Earth at the storm peak.…”
Section: How Do Ring Current and Other Geomagnetic Processes Affect Rmentioning
confidence: 99%
“…Enhanced convection transports moderately energetic particles (ions and electrons) into the inner magnetosphere and accelerates them to form a strong storm-time ring current (e.g., Lyons and Williams 1980;Wolf et al 1997), while time-dependent variations in the large-scale electric field traps particles on closed drift trajectories (e.g., Ejiri 1978). Kinetic model simulations (Jordanova et al 2001aLiemohn et al 2001;Zaharia et al 2010) of ring current development during storms have shown reasonable agreement with the Dst index, indicating the dominant role of magnetospheric convection in ring current energization and trapping. Detailed comparison of modeled ring current distributions, however, showed significant differences at low L, depending on the electric field model being used Yu et al 2012) and highlight the importance of measuring the large-scale electric field.…”
Section: How Do Ring Current and Other Geomagnetic Processes Affect Rmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the reason why coupled models are intensively developed and improved during recent years. Besides several cases considered here, the latest examples include: coupling between the RCM (ring current model) and Versatile Electron Radiation Belt (VERB) code (Subbotin et al, 2011); coupling between RAM-SCB code (ring current model) and BATSRUS/SWMF (MHD with the RCM) (Welling et al, 2011;Zaharia et al, 2010); coupling between two ring current models RAM and the RCM ; one way coupling between MHD Open Geospace General Circulation Model (Open GGCM) -the RCM (ring current model) (Hu et al, 2010). None of these models however is 'ideal' (including the examples presented in detail earlier) in the sense that all of them have some shortcuts.…”
Section: Discussion and Directions For Future Workmentioning
confidence: 99%
“…We simulate the ring current evolution during the double‐dip storm of 7–9 October 2012 using our RAM‐SCB model which couples the ring current‐atmosphere interactions model (RAM) [ Jordanova et al , , ] with the Euler‐potential‐based plasma equilibrium code [ Zaharia et al , , ]. This model has been used successfully in many ring current studies over the past decade; therefore, only a brief description of RAM‐SCB focusing on its recent development is given below.…”
Section: Ram‐scb Model Developmentsmentioning
confidence: 99%